Using the Construct of the Didactic Contract to Understand Student Transition into University Mathematics Education. (June 2014) - Pepin, Birgit
In this article the concept of the Didactic Contract is used to investigate student 'transition' from upper secondary into university mathematics education. The findings are anchored in data from the TransMaths project, more particularly the case of an ethnic minority student's journey from his school to a university mathematics course taught at a large inner-city university in England. Results show that there is a transformation (or rupture) of the Didactic Contract from school to university mathematics, and that this is likely to have serious consequences for students' success, or failure, at this crossroads of students' mathematical development, in particular if students are left to 'bridge the gap' from one contract to the other. Further, the author argues that in order to help to smooth the passage, a refinement of the Didactic Contract is helpful, a re-conceptualisation in terms of Normative Didactic Contract and Personal Didactic Contract, and each needs to be considered at each level of development. This is likely to raise awareness about the necessary conditions for success at both sides of the transition junction, and providing appropriate support for students at both levels is likely to provide access for more students to successfully stay in higher education mathematics.